Nonporous Chitosan/Collagen Scaffold for Skin Tissue Engineering - . Suryati; Harry Agusnar; Saharman Gea; Syafruddin Ilyas (Syiah Kuala University, 2012)
This study aimed to determine film characteristics of chitosan/collagen scaffold for tissue engineering applications. Scaffold prepared using freeze drying method. Surface structure and biological testing chitosan/collagen scaffold crosslinking reagent addition Glutaraldehide studied using Scanning Electron Microscopy test (SEM) and Microscope inverted. Variations in the ratio of chitosan/collagen (10:0, 8:2, 7:3, 6:4, 5:5 4:6, 3:7, 2:8, 0:10), and treated with a crosslinking reagent 0.25% of Glutaraldehyde (GA) of the total weight of the polymer. The next process dissolving and mixing, followed by printing in glass moulds (7,5x7,5) with a thickness of 5 mm. This was followed by the freezing and drying with a freeze dryer. Scaffold chitosan/collagen ratio of 80:20 and a concentration of 0.25% GA showed growth of human skin fibroblast cells most and nonporous surface structure. This study is part of a study of the processing of chitosan/collagen scaffold for applications in tissue engineering